Evaluating the accuracy of morphological identification of insect pests of rice crops using DNA barcoding. Issue 2 (3rd July 2018) - Tahir, Hafiz Muhammad; Noor, Alina; Mehmood, Sana; Sherawat, Sher Muhammad; Qazi, Muhammad Akram
Abstract: Accurate identification of agricultural pests is key requirement for the successful integrated pest management (IPM) program. However, due to limitations of conventional morphological methods, other molecular method like DNA barcoding is used. The current study was designed to evaluate the accuracy of morphological identification of insect pests using DNA barcoding. Morphologically, a total of 247 insect pests, representing 10 families, 18 genera, 22 species were identified. However, molecular identifications confirmed the presence of 11 families, 16 genera, and 20 species of agricultural pests. A total of 59 specimens were processed for DNA barcoding but genomic sequences of mt COI gene up to 600 bp were revived from 48 samples. Specimens that were misidentified through morphological studies were placed to their appropriate taxon, using this molecular approach. Results revealed the existence of clear barcode gap for different pest species. Moreover, the values of distance with the nearest neighbour recorded were higher than the maximum intra-sequence divergences for all species. It is concluded that DNA barcoding is a reliable technique for identification of agricultural pests, especially for immature stages when morphometric studies are ambiguous and will be helpful in the development of more effective pest management options for regulating pest species.